Loan capital as a stimulant of SME developmental investment in the new programming period - Filipiak, Beata Zofia (Kapitał pożyczkowy jako stymulanta inwestycji rozwojowych MŚP w nowym okresie programowania, 2014)
Supporting SMEs development is becoming one of the most significant elements of the country’s policy at various levels: the country as a whole, provinces (regions) or at the very local level. This reflects the EU priorities, the EU policy in the previous decade and it is also becoming a priority in the new programming period for the years 2014–2020. The purpose of the article is to indicate the prerequisites of stimulating the development of SMEs by means of financial instruments (other than banking capital) in the new EU programming period. The article presents the role and importance of loan funds as a financial intermediary supporting the development of SMEs. The paper also presents the idea of a new logic of intervention in the use of funds and construction of financial instruments by loan funds
Biblioteka Regionalisty, 2014, Nr 14, s. 27-38
Keywords: local development; the new programming period; the financing of development; loan capital; rozwój lokalny; finansowanie rozwoju; kapitał pożyczkowy